Hedging Training for Export and Import Business - Margarita Ekadjaja; Amory Takahiro Theja; Wilson Wijaya (Journal of Innovation and Community Engagement, 2023)
Globalization causes changes and provides convenience in trading activities between countries, exports, and imports. This community service program was conducted for a company engaged in the field of iron trading, which deals with imported products from Japan, America, Europe, China, and Taiwan. The main problem faced by this community service partner was the profit uncertainty due to fluctuations in the foreign exchange market. As a way to avoid currency exchange rate uncertainty, companies can hedge. One of the hedging activities carried out by company management in dealing with fluctuations in foreign exchange rates is the alternative use of derivative instruments. The method for implementing the community service activities was in the form of onsite training which was divided into two sessions. In the first session, the community service team gave a lecture on a general overview of hedging. In the second session, the community service team carried out a simulation of calculating the costs of hedging using appropriate tools. This community service program provides results in the form of developing partner's know-how that provides benefits to mitigate risk through hedging capabilities. Based on the simulation results using the hedging cost calculation tool, partners can see that hedging in the money market is more profitable than forward contracts.